2009
DOI: 10.1016/j.jvs.2009.07.109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of peripheral arterial disease on health status: A comparison with chronic heart failure

Abstract: By contrasting PAD patients' health status with another chronic disabling condition, the impact of PAD on patients' physical health status became evident; whereas mental health status was more affected in CHF, patients with PAD reported a greater physical burden as compared with CHF patients. PAD patients who were younger, lower-educated, without a partner or had a cardiac history especially reported a higher disease burden. Clinicians need to be aware of these differences in order to develop tailor-made disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…23 The SF‐12 has been demonstrated to be a valid and reliable instrument 20 and has been successfully utilized in PAD populations. 2425 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The SF‐12 has been demonstrated to be a valid and reliable instrument 20 and has been successfully utilized in PAD populations. 2425 …”
Section: Methodsmentioning
confidence: 99%
“…23 The SF-12 has been demonstrated to be a valid and reliable instrument 20 and has been successfully utilized in PAD populations. 24,25 Depressive symptoms The 14-item self-report Hospital Anxiety and Depression Scale was used to measure self-reported depressive symptoms. Criterion scores of ≥8 for the depression subscale denote clinically relevant symptoms of depression.…”
Section: Health Statusmentioning
confidence: 99%
“…28 It was designed to be a simpler version of the SF-36, scored in the same way as the SF-36. Using the SF-12, Smolderen et al 29 assessed baseline HRQOL of symptomatic PAD patients compared to chronic heart failure patients. Results indicated that the physical domains were affected to a greater extent in PAD patients, whereas the mental domains were significantly worse in chronic heart failure patients.…”
Section: Functional Status/hrqol Questionnaires For Symptomatic Padmentioning
confidence: 99%
“…12 Additionally, MCS scores in patients with a neuropathic component were comparable to scores in patients with severe chronic obstructive pulmonary disease and congestive heart failure. 13,14 The limitations of our study include the inherent bias associated with self-reported data. Patients presenting to the physician office complete surveys based on symptoms at the time of completion.…”
Section: S-lanss Scores In Patients Withmentioning
confidence: 97%